2019
DOI: 10.1002/cnma.201900159
|View full text |Cite
|
Sign up to set email alerts
|

COF‐Derived N,P Co‐Doped Carbon as a Metal‐Free Catalyst for Highly Efficient Oxygen Reduction Reaction

Abstract: A new kind of metal‐free, porous, and N,P co‐doped carbon catalyst was prepared from a high crystalline and two dimensional (2D) covalent organic framework (COF). Remarkably, this N,P co‐doped catalyst exhibits an excellent tolerance towards methanol crossover, as well as a comparable oxygen reduction reaction performance to commercial Pt/C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…[20] P doping also enhances edge defects by introducing surface defects. [21] Theoretical analysis further revealed that edge-doped sites with N, P dopants are more efficient to improve ORR, compared with the inner doped ones, highlighting synergistic effect of edge defects and heteroatom doping. [13] Additionally, the well-balanced pore structure, high surface area and good conductivity are also of importance in boosting the catalytic performance of an electrocatalyst.…”
Section: Introductionmentioning
confidence: 95%
“…[20] P doping also enhances edge defects by introducing surface defects. [21] Theoretical analysis further revealed that edge-doped sites with N, P dopants are more efficient to improve ORR, compared with the inner doped ones, highlighting synergistic effect of edge defects and heteroatom doping. [13] Additionally, the well-balanced pore structure, high surface area and good conductivity are also of importance in boosting the catalytic performance of an electrocatalyst.…”
Section: Introductionmentioning
confidence: 95%
“…192,193 There have been many breakthrough applications for this technology in batteries. 192,[194][195][196][197][198][199] Wang et al 200 reported a new metalo-covalent organic framework doped with Ag/Ag 2 O. This MCOF combines the advantages of MOFs and COFs and provides excellent OER and ORR performance through synergistic interaction between Co, O, N, Ag/Ag 2 O and a nano-ower-like structure, as shown in Fig.…”
Section: Organic-based Framework Air Electrodementioning
confidence: 99%
“…58,62,63 So far, numerous studies have shown that P-doped nonmetal carbon based ORR catalysts show excellent ORR activity. 64,65 Yang et al 60 synthesized a kind of N and P co-doped non-metal carbon catalyst, and its active structure was Fig. 2 (a) The P-doping configuration.…”
Section: P-doped M-n-c Sacsmentioning
confidence: 99%